2018
DOI: 10.1186/s12909-018-1180-8
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate medical students’ perceptions and intentions regarding patient safety during clinical clerkship

Abstract: BackgroundThe purpose of this study was to examine undergraduate medical students’ perceptions and intentions regarding patient safety during clinical clerkships.MethodsCross-sectional study administered in face-to-face interviews using modified the Medical Student Safety Attitudes and Professionalism Survey (MSSAPS) from three colleges of medicine in Korea. We assessed medical students’ perceptions of the cultures (‘safety’, ‘teamwork’, and ‘error disclosure’), ‘behavioural intentions’ concerning patient safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 25 publications
3
26
0
2
Order By: Relevance
“…Although none of the respondents had received formal patient-safety instruction, more than half were confident in reporting errors regardless of who made them. This was similar to the findings of previous studies [2,9,10]. However, over half were also afraid of initiating discussions as junior members.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although none of the respondents had received formal patient-safety instruction, more than half were confident in reporting errors regardless of who made them. This was similar to the findings of previous studies [2,9,10]. However, over half were also afraid of initiating discussions as junior members.…”
Section: Discussionsupporting
confidence: 91%
“…However, the idea of patient safety is still underdeveloped in the context of undergraduate medical education, especially true in Korea. One Korean study found that 73.7% of all respondents positively assessed the importance of medical error disclosure, but that less than 20% had received education or training on how to disclose errors and thus had negative perceptions of the error disclosure culture [2].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that error reporting guidelines and educational methods aiming to develop better communication skills need to be taught at the undergraduate level to improve patient safety. [9] Awareness of the protocols of safety being used in a health-care organization is the first step to identifying any areas for improvement, since the knowledge, attitudes, and behaviors of health-care staff are critical in the culture of safety, as seen in an Italian study. [10] In a study published in the Journal of Surgical Education, the authors delivered a patient safety course for 1 week-2 nd -year medical students.…”
Section: Discussionmentioning
confidence: 99%
“…It seeks to meet the national guidelines proposing emancipation and autonomy based on ethical-professional principles. During the course, the methodology of learning is based on problems and, as another guiding axis of the curriculum, the questioning, whose epistemological justification relates to the paradigm of community educational organization, participatory and democratic (Lee, Hahm, & Lee, 2018).…”
Section: Discussionmentioning
confidence: 99%